Viromes of Tabanids from Russia - Litov, Alexander G.; Belova, Oxana A.; Kholodilov, Ivan S.; Kalyanova, Anna S.; Gadzhikurbanov, Magomed N.; Rogova, Anastasia A.; Gmyl, Larissa V.; Karganova, Galina G. (Viruses, 2023)
Advances in sequencing technologies and bioinformatics have greatly enhanced our knowledge of virus biodiversity. Currently, the viromes of hematophagous invertebrates, such as mosquitoes and ixodid ticks, are being actively studied. Tabanidae (Diptera) are a widespread family, with members mostly known for their persistent hematophagous behavior. They transmit viral, bacterial, and other pathogens, both biologically and mechanically. However, tabanid viromes remain severely understudied. In this study, we used high-throughput sequencing to describe the viromes of several species in the Hybomitra, Tabanus, Chrysops, and Haematopota genera, which were collected in two distant parts of Russia: the Primorye Territory and Ryazan Region. We assembled fourteen full coding genomes of novel viruses, four partial coding genomes, as well as several fragmented viral sequences, which presumably belong to another twelve new viruses. All the discovered viruses were tested for their ability to replicate in mammalian porcine embryo kidney (PEK), tick HAE/CTVM8, and mosquito C6/36 cell lines. In total, 16 viruses were detected in at least one cell culture after three passages (for PEK and C6/36) or 3 weeks of persistence in HAE/CTVM8. However, in the majority of cases, qPCR showed a decline in virus load over time.